Dlx1 transcription factor regulates dendritic growth and postsynaptic differentiation through inhibition of neuropilin‐2 and PAK3 expression. (15th November 2013) - Dai, Xiaojing; Iwasaki, Hirohide; Watanabe, Masahiko; Okabe, Shigeo
Abstract Dlx1, a member of the homeobox domain transcriptional factors, is expressed in a subset of interneurons and is involved in their differentiation. To understand the roles of Dlx1 in dendritic and postsynaptic differentiation, we manipulated Dlx1 expression in both excitatory pyramidal neurons and inhibitory interneurons in hippocampal culture. Exogenous expression of Dlx1 in pyramidal neurons, which lack endogenous Dlx1, resulted in reduced complexity of dendritic arborization. This effect was dependent on the DNA‐binding motif of Dlx1. Dlx1 overexpression also induced prominent reduction of spine density, but with mild suppression in the formation of postsynaptic densities. To confirm the roles of endogenous Dlx1, we knocked down Dlx1 in interneurons and found enhanced dendritic growth. By manipulating the expression of possible downstream effectors of Dlx1, neuropilin‐2 and p21‐activated kinase 3, we provided evidence for the involvement of these two signaling molecules in Dlx1‐dependent regulation of dendritic differentiation. Our experimental data support the idea that Dlx1 expression in developing interneurons specifically suppresses two important downstream regulators, leading to the characteristic morphology of Dlx1‐expressing interneurons with less branched dendrites and few dendritic spines.